Educational Modalities for Teaching Surgical Techniques for Obstetric Anal Sphincter Injuries: A Randomized Trial [09G]. (May 2020) - Jackson, Lindsey; Byrne, John J.; Lupo, Andrew; Florian-Rodriguez, Maria; Wai, Clifford; Balgobin, Sunil
Abstract : INTRODUCTION: Decreasing rates of obstetrical anal sphincter injuries (OASIS) has posed challenges for the clinical training of residents in repairing this highly morbid injury. The aim of this study is to compare an OASIS repair model to an educational video for resident education. METHODS: IRB Exemption was obtained. OB/GYN residents completed a baseline questionnaire and written knowledge test evaluating OASIS epidemiology, anatomy, complications, and surgical technique. In addition, they performed a baseline graded hands-on repair with a beef tongue model using a validated objective structured assessment of technical skills (OSATS). Subjects were randomized to either viewing an OASIS educational video ("video") or attending a workshop using a synthetic anal sphincter trainer model ("model"). 6-10 weeks later, post-intervention knowledge and practical assessments were completed. RESULTS: 53 residents (n=28 "video, " n=25 "model") participated in the study. There were no pre-intervention differences in knowledge or skill scores between groups. Mean±SD knowledge and skill scores improved from baseline regardless of intervention (Model knowledge 6±2 vs 8±2, P= .01, skill 14±3 vs 18±1, P <.01; Video knowledge 6±1 vs 8±2, P =.03, skill -14±2 vs 16±1, P< .01). The "model" group had greater improvement in skill level than the "video" group (18±1 vs 16±1, P <.01). By training level, all but the PGY-4 class significantly improved ( P< .05). 100% of residents in model group and 92% in video group believed the intervention to be very educational. CONCLUSION: Although both educational modalities improve OASIS knowledge and skills, the model is more effective at improving technical skills.